2021
DOI: 10.1108/ijqss-11-2020-0172
|View full text |Cite
|
Sign up to set email alerts
|

The role of switching cost in the e-service recovery framework among banking customers

Abstract: Purpose The emergence of tech-driven initiatives in retail banking has created a vast spectrum of system-related service failures; hence, e-service recovery quality is of prime importance to banks to ensure e-service recovery satisfaction. However, e-service satisfaction is dependent on the ease of moving from one service provider to the other; thus, switching costs assume great significance. This study aims to probe the moderating role of switching cost on e-service recovery satisfaction by exploring e-servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…Studies conducted by Butt and Aftab (2013), Mbama and Ezepue (2018) and Raza et al (2020) have explored the relationship between e-service quality, e-satisfaction, e-loyalty, e-retention and e-WOM. Jose et al (2021) found that the recovery expectation is a significant predictor of e-customer satisfaction, and of e-retention, which is moderated by the switching cost. Factors such as web architecture, user friendliness, efficiency of the website, reliability, responsiveness, security and personalization play an important role in the e-banking service quality and customer satisfaction (Mir et al , 2022).…”
Section: Review Of the Research Streams In The Bsq Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…Studies conducted by Butt and Aftab (2013), Mbama and Ezepue (2018) and Raza et al (2020) have explored the relationship between e-service quality, e-satisfaction, e-loyalty, e-retention and e-WOM. Jose et al (2021) found that the recovery expectation is a significant predictor of e-customer satisfaction, and of e-retention, which is moderated by the switching cost. Factors such as web architecture, user friendliness, efficiency of the website, reliability, responsiveness, security and personalization play an important role in the e-banking service quality and customer satisfaction (Mir et al , 2022).…”
Section: Review Of the Research Streams In The Bsq Literaturementioning
confidence: 90%
“…Factors such as web architecture, user friendliness, efficiency of the website, reliability, responsiveness, security and personalization play an important role in the e-banking service quality and customer satisfaction (Mir et al , 2022). Some recent studies (Jose et al , 2021; Chauhan et al , 2022; Hanafizadeh and Amin, 2022; Ighomereho et al , 2022; Simmers et al , 2022) have explored the relationship of Internet banking service quality. This domain has been explored to an extent, and still, there is scope for further exploration.…”
Section: Review Of the Research Streams In The Bsq Literaturementioning
confidence: 99%